Evaluation systems and their indicators in Legislations Constructivist as a standard In Shaping the urban environment in the regions of southern Algeria Through Executive Decree No. 14/27 of February 01, 2014. The city of a thousand domes and domes - Oued Souf - a model - Halima, Zidani; Assassi, Abdelhalim (Technium Social Sciences Journal, 2022)
One of the reasons for the failure of urban development in the desert city in Algeria is the stability of construction legislation and its inability to change to keep pace with the requirements of the environment and society and the data of the times, In light of this legislative default, the desert city in Algeria today suffers from the loss of its identity and its urban and architectural specificity, Which leads to an increasing need to adopt trends to achieve a positive relationship between the quality of residential programs and the desert environment , From this point of view, Algeria has Strengthened this legislative orientation by issuing Executive Decree No. 14/27 of February 01, 2014, which defines the urban, architectural and technical specifications applicable to buildings in the states of the south, With the advent of the concept of sustainability and its evaluation systems, Then Algeria has adopted this approach as an orientation in shaping the urban environment, Through the directive law of the city in the Framework Territory initialization and sustainable development Dated February 20, 2006, To become Sustainability becomes an approach to any development process, so research in its relationship to building legislation is a starting point for sustainable design , Therefore, our study came to search first the extent to which the specifications of this executive decree and the idea of sustainability are compatible through the terms of the LEED-NC evaluation system, which includes a set of criteria that must be met to achieve the sustainability of the building, Then review he features of its applications Through the project of 100 residences in Oued Souf city, And the results of the study showed us That there is a compatibility between the idea of sustainability and what the executive decree poses in terms of urban, architectural and technical specifications , So It came he compatibility With the items of the evaluation system LEED-NC was 56.14%, despite the lack of he embed For many system standards , This means That executive decree Can be used as a reference for achieving sustainable Algerian architecture If it is adapted to sustainability criteria, And because the analytical study of the 100 housing project in Oued Souf city It excreted in shortcomings in implementing the requirements of its his specifications by 12.28%,As it includes the standards of the system, the matter summons for the creation of legal oversight mechanisms that work to implement the specifications approved by any proposed legislative methodology in the production of buildings that achieve the foundations of sustainable design in the desert environment in Algeria.